Design and Development of a Digital Weight Management Intervention (ToDAy): Qualitative Study - Shoneye, Charlene; Mullan, Barbara; Begley, Andrea; Pollard, Christina; Jancey, Jonine; Kerr, Deborah (JMIR Publications, 2020)
Background: The Tailored Diet and Activity (ToDAy) study aims to build on the campaign by adding a digital intervention with the potential to provide wide-reaching, cost-effective weight management support.